Evidence-based medicine 1: Background. Issue 1 (February 2019) - Fossum, M.; Herbst, K.; Harper, L.; Castagnetti, M.; Beckers, G.; Bagli, D.; Kalfa, N.; Kaefer, M.; ,
Summary: The Research Committee of the European Society of Pediatric Urology will present a series of short educational communications related to evidence-based medicine. The aim of the series is to emphasize the importance of grading evidence, thereby determining the best clinical practice for patients. The goal of this series is to guide the clinician in using tools for setting up a clinical question, finding appropriate information, searching appropriate databases, and evaluating the results in relation to the patient in mind. This first part will serve as an introduction or background. Following publications will cover the topics of hierarchy of evidence, information acquisition, clinical appraisal tools, and applications in clinical practice[3] .